2001
DOI: 10.1016/s0736-0266(00)90027-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles of abdominal and back muscles during isometric axial rotation of the trunk

Abstract: Electromyographic (EMG) studies have shown that a large number of trunk muscles are recruited during axial rotation. The functional roles of these trunk muscles in axial rotation are multiple and have not been well investigated. In addition, there is no information on the coupling torque at different exertion levels during axial rotation. The aim of the study was to investigate the functional roles of rectus abdominis, external oblique, internal oblique, latissimus dorsi, iliocostalis lumboruni and multifidus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 47 publications
6
52
1
3
Order By: Relevance
“…The average T max of the neck muscles has been estimated at 15 Nm in males and 6 Nm in females (Vasavada et al 1998). The average T max of the trunk muscles has been estimated at 97 Nm in standing males and 60 Nm in females (Kumar and Panjabi 1995;Kumar et al 2001;McGill and Hoodless 1990;Ng et al, 2001;Perez and Nussbaum 2002). Finally, the average T max of internal hip rotation has been estimated to be 60% of that of the trunk in males and 65% in females (Stoll et al 2000).…”
Section: Relation Between Axial Torque and The Level Of Tonementioning
confidence: 99%
“…The average T max of the neck muscles has been estimated at 15 Nm in males and 6 Nm in females (Vasavada et al 1998). The average T max of the trunk muscles has been estimated at 97 Nm in standing males and 60 Nm in females (Kumar and Panjabi 1995;Kumar et al 2001;McGill and Hoodless 1990;Ng et al, 2001;Perez and Nussbaum 2002). Finally, the average T max of internal hip rotation has been estimated to be 60% of that of the trunk in males and 65% in females (Stoll et al 2000).…”
Section: Relation Between Axial Torque and The Level Of Tonementioning
confidence: 99%
“…This implies that trunk muscles create a twisting moment that is opposite to the moment resulting from the push-off forces. External oblique (EO) and internal oblique (IO) muscles are the main contributors to twisting moments (Dumas et al, 1991;Ng et al, 2001;Kumar et al, 2003) and these muscles are cyclically active during normal gait (Callaghan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This result may imply that RA did not have a direct functional role in sustaining ASLR in different hip positions in frontal plane in healthy subjects. A previous study also reported that rectus abdominis showed no functional role during isometric axial rotation of the trunk (Ng et al, 2001). …”
Section: Discussionmentioning
confidence: 86%